2016
DOI: 10.1037/rel0000049
|View full text |Cite
|
Sign up to set email alerts
|

Exploring emerging adults’ relational spirituality: A longitudinal, mixed-methods analysis.

Abstract: Using a longitudinal, mixed-methods design and building on Shults and Sandage's (2006) relational spirituality model, we explored spiritual seeking, spiritual dwelling, and the dialectical process of balancing spiritual seeking and dwelling. Assessing a sample of 77 Christian emerging adults twice over a 2-year period (thirty-nine 2006 graduates and thirty-eight 2008 graduates), we quantitatively measured spiritual seeking (using the Quest Scale) and qualitatively measured spiritual dwelling (using narratives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…As the social world of emerging adults change, many may begin to question or doubt their faith (Hall, Edwards, and Wang 2016; Haney and Rollock 2020; Kimball et al. 2016; Liang and Ketcham 2017; Zarzycka and Zietek 2019). However, less is known about the mechanisms through which religious doubt impacts well‐being in emerging adulthood, and no prior study has utilized a nationally representative, longitudinal sample of emerging adults.…”
Section: Introductionmentioning
confidence: 99%
“…As the social world of emerging adults change, many may begin to question or doubt their faith (Hall, Edwards, and Wang 2016; Haney and Rollock 2020; Kimball et al. 2016; Liang and Ketcham 2017; Zarzycka and Zietek 2019). However, less is known about the mechanisms through which religious doubt impacts well‐being in emerging adulthood, and no prior study has utilized a nationally representative, longitudinal sample of emerging adults.…”
Section: Introductionmentioning
confidence: 99%
“…The seeking involved in contemplative approaches is certainly consistent with Myers and Willard's (2003) contention that spirituality is an impulse toward personal growth, and even more so with Hermans and Koerts's (2013) position that spirituality is growing in discernment. Less clear is the relationship of the current findings with definitions of spirituality as connection, such as de Jager Meezenbroek et al (2012) and Garssen, Visser, and de Jager Meezenbroek (2016), who focused on connectedness with the "essence of life" in terms of self, others, nature, and a non-theistic "transcendent" (de Jager Meezenbroek et al, 2012, p. 142), and Kimball et al (2016), who identified spirituality with transcendence and a relationship to the sacred, including ultimate truth. Connectedness and relationship inherently involve Wade duality.…”
Section: Discussionmentioning
confidence: 78%
“…Researchers developing the Spiritual Attitude and Involvement List (SAIL;de Jager Meezenbroek, et al, 2012) for working with patients with life-threatening conditions focused on connecting with the "essence of life," especially connectedness with self, others, nature, and the transcendent (p. 142), which they do not equate with God (Garssen, Visser, & de Jager Meezenbroek, 2016). Another review (Kimball, Cook, Boyatzis, & Leonard, 2016) cited trends that identify spirituality with transcendence (notably Elkins, Hedstrom, Hughes, Leaf, & Saunders, 1988) and that involve a relationship to the "sacred," signifying entities representing ultimate truth and devotion, including God (notably Hill & Pargament, 2003;Shults & Sandage, 2006;Pargament, 2007). According to Hitzhusen (2004), spirituality "can involve transcendence, ineffability, mystery, feelings 'deep in one's soul,' beauty, goodness, contemplation, a sense of inspiration or renewal, encounter with sublime natural settings, and intuition of the divine; it is often characterized by a sense of awe, unity, personal balance, or inner peace" (p. 41).…”
Section: International Journal Of Transpersonal Studies 91mentioning
confidence: 99%
“…He distinguishes four spaces of sense to which he belongs: work/achievements, intimacy/relationship, spirituality/religiosity and auto-transcendence. Empirical research supports the notion that religion is associated with a sense of meaning in life in different ways during the lifespan development (Bailey et al, 2016;Emmons & Schnitker, 2013;Kimball et al, 2016;Mattis, 2002). Steger et al (2008) emphasize the need to differentiate time perspective in studies on the presence of meaning in life and the search for that meaning.…”
Section: Meaning In Life Positive Orientation To Life and Gratitude As Indicators Of Quality Of Lifementioning
confidence: 84%